Digital, Crowdsourced, Multilevel Intervention to Promote HIV Testing Among Men Who Have Sex With Men: Cluster Randomized Controlled Trial - Yuxi Lin; Ci Ren; Meizhen Liao; Dianmin Kang; Chuanxi Li; Kedi Jiao; Lin Wang; Yu Yan; Yijun Li; Taoyu Wu; Chunxiao Cheng; Zhe Zhao; et al. (JMIR Publications, 2023)
BackgroundDespite great efforts in HIV prevention worldwide, HIV testing uptake among men who have sex with men (MSM) remains suboptimal. The effectiveness of digital, crowdsourced, multilevel interventions in improving HIV testing is still unclear. ObjectiveThe aim of this study was to evaluate the effect of a digital, crowdsourced, multilevel intervention in improving HIV testing uptake among MSM in China. MethodsWe conducted a 2-arm cluster randomized controlled trial among MSM in 11 cities in Shandong province, China, from August 2019 to April 2020. Participants were men who were HIV seronegative or had unknown serum status, had anal sex with a man in the past 12 months, and had not been tested for HIV in the past 3 months. Participants were recruited through a gay dating app and community-based organizations from preselected cities; these cities were matched into 5 blocks (2 clusters per block) and further randomly assigned (1:1) to receive a digital, crowdsourced, multilevel intervention (intervention arm) or routine intervention (control arm). The digital multilevel intervention was developed through crowdsourced open calls tailored for MSM, consisting of digital intervention images and videos, the strategy of providing HIV self-testing services through digital tools, and peer-moderated discussion within WeChat groups. The primary outcome was self-reported HIV testing uptake in the previous 3 months. An intention-to-treat approach was used to examine the cluster-level effect of the intervention in the 12-month study period using generalized linear mixed models and the individual-level effect using linear mixed models. ResultsA total of 935 MSM were enrolled (404 intervention participants and 531 controls); 751 participants (80.3%) completed at least one follow-up survey. Most participants were younger than 30 years (n=601, 64.3%), single (n=681, 72.8%), had a college degree or higher (n=629, 67.3%), and had an HIV testing history (n=785, 84%). Overall, the proportion of testing for HIV in the past 3 months at the 3-, 6-, 9-, and 12-month follow-ups was higher in the intervention arm (139/279, 49.8%; 148/266, 55.6%; 189/263, 71.9%; and 171/266, 64.3%, respectively) than the control arm (183/418, 43.8%; 178/408, 43.6%; 206/403, 51.1%; and 182/397, 48.4%, respectively), with statistically significant differences at the 6-, 9-, and 12-month follow-ups. At the cluster level, the proportion of participants who had tested for HIV increased 11.62% (95% CI 0.74%-22.5%; P=.04) with the intervention. At the individual level, participants in the intervention arm had 69% higher odds for testing for HIV in the past 3 months compared with control participants, but the result was not statistically significant (risk ratio 1.69, 95% CI 0.87-3.27; P=.11). ConclusionsThe intervention effectively improved HIV testing uptake among Chinese MSM. Our findings highlight that digital, crowdsourced, multilevel interventions should be made more widely available for HIV prevention and other public health issues. Trial RegistrationChinese Clinical Trial Registry ChiCTR1900024350; http://www.chictr.org.cn/showproj.aspx?proj=36718. International Registered Report Identifier (IRRID)RR2-10.1186/s13063-020-04860-8